A Low Dose of Naloxone Added to Ropivacaine Prolongs Femoral Nerve Blockade: A Randomized Clinical Trial - Seung Cheol Lee; Jeong Ho Kim; So Ron Choi; Sang Yoong Park (Pain Research and Management)
Femoral nerve blocks (FNBs) are used as safe and useful procedures to control severe postoperative pain from total knee arthroplasty (TKA). Various adjuvants have been used to prolong the duration of the local anesthetic blockade. This study evaluated whether a low dose of naloxone administered with local anesthetics prolongs the duration of FNB. A prospective, randomized double-blind controlled study was conducted with 74 patients undergoing unilateral TKA. Through a single-bolus administration guided by ultrasound, the control group (group C) received 20 mL of 0.375% ropivacaine, while the naloxone group (group N) received 20 mL of 0.375% ropivacaine with 100 ng of naloxone. The time elapsed before the first analgesia request, the total amount of opioids consumed at 24 h postoperatively, the onset time of the sensory blockade, the visual analog pain scale (VAS) scores after arriving at the recovery room, after 6, 12, 18, and 24 h at rest and after 12, 18, and 24 h of activity, the quadricep strength before the FNB procedure and at 12 and 24 h postoperatively, the quality of sleep on the first night after surgery, the satisfaction score, and the incidence of postoperative complications were recorded. The time elapsed before the first analgesia request was significantly longer in group N (735.5 ± 187.2 min) than that in group C (602.6 ± 210.4 min) (P=0.003). The total dose of supplementary opioids consumed at 24 h postoperatively was significantly lower in group N (312.4 ± 141.7 μg) than that in group C (456.5 ± 279.5 μg) (P=0.007). Lower VAS scores were recorded in group N than that in group C at rest and during knee activity (rest, 12 h, P=0.001, 18 h, P=0.043; activity, 12 h, P=0.001). The addition of a low dose of naloxone to ropivacaine for FNB significantly delayed the first request for rescue analgesia and decreased the opioid consumption within 24 h, without significant complications.